Opening the Black Box of Carbon Finance "Additionality": The Political Economy of Carbon Finance Effectiveness across Tanzania, Uganda, and Moldova. (October 2015) - Purdon, Mark
Summary: This paper identifies conditions under which the Clean Development Mechanism and other carbon finance projects effectively generate genuine, "additional" carbon credits—relying on a systematic empirical investigation of afforestation/reforestation and bioenergy carbon finance projects across Tanzania, Uganda, and Moldova. At low global carbon prices, additionality was related to the interests of project developers and their resulting capacities and motivations for project implementation. Certain organizations with capacity for mitigation projects were curiously not involved with carbon finance. A distinction between neo-developmental (Tanzania) and liberal neo-developmental (Uganda and Moldova) political economy preferences explains variation in the presence or absence of effective project developers.